A new balanced‐to‐single‐ended in‐phase filtering power divider based on circular patch resonator with good isolation and wide stopband. Issue 10 (2nd August 2021) - Zhang, Qiyun; Zhang, Gang; Liu, Zhengkang; Tan, Xinrong; Tang, Wanchun; Yang, Hua
Abstract: In this article, a novel balanced‐to‐single‐ended (BTSE) in‐phase filtering power divider (FPD) based on circular patch resonator with good isolation and wide stopband is proposed. In this design, by carefully exploring the electric field distributions of the microstrip circular patch resonator modes, the common‐mode can be well suppressed at the balanced ports, while in‐phase output and good isolation can be attained at the single‐ended ports. At the same time, filtering response is formed by coupling two circular patches through a circular aperture etched on the common ground. To verify the feasibility of this concept, a BTSE in‐phase FPD operating at 4.2 GHz with 3‐dB fractional bandwidth (FBW) of 19% is designed, manufactured, and tested. The consistency between the simulation results and the measurement results is good, indicating that this design has expected differential‐mode response, nice common‐mode suppression, significant single‐ended output port isolation, as well as wide stopband.